Risk of resistance evolution of Spodoptera frugiperda (Lepidoptera: Noctuidae) to emamectin benzoate in Brazil - Muraro, Dionei Schmidt (2022)
The use of chemical insecticides is one of the main strategies to control Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) in Brazil. However, the reduction in the efficiency of insecticides due to the evolution of resistance has been one of the major challenges in the implementation of integrated pest management programs. Among the insecticides, emamectin benzoate from the avermectin group represents an important option for the management of S. frugiperda. This insect pest can cause severe damage to several crops of economic importance, if control strategies are neglected. In this sense, studies that promote the implementation of insect resistance management (IRM) strategies are essential to maintain the efficacy of emamectin benzoate against S. frugiperda. The goals of this study were: (i) monitoring of susceptibility to emamectin benzoate in populations of S. frugiperda in Brazil (ii) selection and characterization of the inheritance pattern, cross-resistance and synergism in S. frugiperda resistant to emamectin benzoate; and (iii) Assessment of fitness cost in S. frugiperda resistant to emamectin benzoate. Monitoring was carried out on S. frugiperda populations collected in the field from 2019 to 2021 in compare to the baseline susceptibility studies conducted with populations collected in 2003 and 2004. From 2003 to 2004, larval survival at the diagnostic concentration of emamectin benzoate (3.2 μg a.i./mL) was < 1.79%. From 2019 to 2021, susceptibility to emamectin benzoate in S. frugiperda decreased, with LC50 values ranging from 0.78 to 158.0 μg a.i. mL-1 (resistance ratios up to 632-fold). Using the diagnostic concentration, we also observed an increase in larval survival of up to 81.4%. Larval survival on maize leaves sprayed with the field rate of emamectin benzoate ranged from 16.6 to 88.5% in populations of S. frugiperda collected in 2021. The emamectin benzoate resistant strain was selected using the F2 screen method and after 10 generations of selection pressure this strain showed a resistance ratio of 2,339-fold. The inheritance of emamectin benzoate resistance in S. frugiperda was characterized as autosomal, incompletely dominant, and polygenic. Low cross-resistance was observed among emamectin benzoate and other insecticides (methomyl, chlorpyrifos, lambda-cyhalothrin, spinetoram, indoxacarb and chlorantraniliprole), ranging from 1.1 to 5.7-fold. In addition, the exposure of the strains to different synergists known to inhibit detoxification enzymes did not result in significantly increased larval toxicity, suggesting a minor role for metabolic resistance. Also, we observed fitness cost associated with the resistance of S. frugiperda to emamectin benzoate, reducing ∽35% its potential for population growth on non-Bt maize and artificial diet. In contrast, a lack of fitness cost was observed in the behavioral parameters, including mobility time, distance traveled, speed, and predation rate by Podisus nigrispinus (Heteroptera: Pentatomidae). The results of this study demonstrate the risk of resistance evolution of S. frugiperda to emamectin benzoate in Brazil. Therefore, the information obtained in this study showed high risk of resistance evolution of S. frugiperda to emamectin benzoate and IRM strategies should be implemented to prolong the lifetime of this insecticide in the management of S. frugiperda in Brazil.